2021
DOI: 10.5194/nhess-21-3353-2021
|View full text |Cite
|
Sign up to set email alerts
|

Tidal flood area mapping in the face of climate change scenarios: case study in a tropical estuary in the Brazilian semi-arid region

Abstract: Abstract. Previous studies on tidal flood mapping are mostly through continental- and/or global-scale approaches. Moreover, the few works on local-scale perception are concentrated in Europe, Asia, and North America. Here, we present a case study approaching a tidal flood risk mapping application in the face of climate change scenarios in a region with a strong environmental and social appeal. The study site is an estuarine cut in the Brazilian semi-arid region, covering part of two state conservation units, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The geosites present in the other protected areas are also exposed to this type of consequence, enhanced by climate change (Figure 26). Aguiar et al [21] evaluated the risk of tidal inundation due to climate change in the Apodi-Mossoró estuary, sector to the west of the Dunas do Rosado EPA and to the southeast of the Arrombado EPA and found a risk situation similar to that indicated by Araújo et al [59]. Aguiar et al [21] identified that flooding events can result in orders in excess of USD 147,000 and climate change scenarios show trends in increased flooding.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The geosites present in the other protected areas are also exposed to this type of consequence, enhanced by climate change (Figure 26). Aguiar et al [21] evaluated the risk of tidal inundation due to climate change in the Apodi-Mossoró estuary, sector to the west of the Dunas do Rosado EPA and to the southeast of the Arrombado EPA and found a risk situation similar to that indicated by Araújo et al [59]. Aguiar et al [21] identified that flooding events can result in orders in excess of USD 147,000 and climate change scenarios show trends in increased flooding.…”
Section: Resultsmentioning
confidence: 91%
“…Araújo et al [59] highlight the presence of signs of sea level rise in coastal municipalities that encompass both the Dunas do Rosado EPA and the Ponta do Tubarão SDR. The results of this research show that 16% of the study area presents high to extremely high vulnerability to tidal flooding, corresponding to 205.30 km 2 .…”
Section: Resultsmentioning
confidence: 99%
“…These ocean tides are primarily caused by gravitational forces and play a crucial role in modelling extreme conditions within estuary. Furthermore, [Araújo] stated that high tides are important to consider in modelling coastal flooding [9].…”
Section: Sea Levelmentioning
confidence: 99%
“…These ocean tides are primarily caused by gravitational forces and play a crucial role in modelling extreme conditions within estuary. Furthermore, Araújo et al (2021) stated that high tides are important to consider in modelling coastal flooding.…”
Section: Sea Levelmentioning
confidence: 99%
“…This consideration is important to avoid underestimating the risk of flooding in an area, as coinciding hazards can have a more significant impact than separate occurrences. Additionally, accurate mapping of flood extent, vulnerability, and risk play a crucial role in the planning and implementing of interventions in flood-prone areas (Araújo et al, 2021). This research evaluated the effectiveness of coastal and river embankment under compound hazards conditions.…”
Section: Introductionmentioning
confidence: 99%